2018
DOI: 10.1097/md.0000000000010493
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of gastric cancer-related ischemic stroke and its underlying pathogenesis

Abstract: This study aimed to investigate the biomarkers and underlying pathogenesis of ischemic stroke in patients with gastric cancer (GC).Patients with active gastric cancer who had experienced acute ischemic stroke without conventional vascular risk factors (gastric cancer-related stroke [GCS] group) and visited The First Affiliated Hospital of Guangxi Medical University and First Affiliated Hospital of Sun Yat-sen University from January 2003 to December 2016 were retrospectively enrolled. The patients’ clinical fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Mean age of study participants ranged from 34.9 to 73.2 years. Some studies focused on patients with specific diseases including diabetic patients in 6 studies [ 14 , 16 , 23 , 30 , 43 , 44 ], gastric cancer in 1 study [ 40 ], CKD patients in 2 studies, and HIV patients in 1 study [ 47 ]. Percentages of patients having DM, HT, and DLP and smoking ranged within 0%-100%, 5.9%-80.9%, 12.4%-83.9%, and 0%-45.8%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean age of study participants ranged from 34.9 to 73.2 years. Some studies focused on patients with specific diseases including diabetic patients in 6 studies [ 14 , 16 , 23 , 30 , 43 , 44 ], gastric cancer in 1 study [ 40 ], CKD patients in 2 studies, and HIV patients in 1 study [ 47 ]. Percentages of patients having DM, HT, and DLP and smoking ranged within 0%-100%, 5.9%-80.9%, 12.4%-83.9%, and 0%-45.8%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Among 10 studies of 58,867 participants, 2 studies [ 33 , 39 ] reported OR of high versus low NLR, 6 studies [ 35 , 37 , 38 , 40 42 ] reported mean differences between stroke patients and controls, and 2 studies [ 34 , 36 ] reported both. Types of stroke were ischemic stroke and TIA.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several studies found PNR was correlated with thrombosis [ 14 ]. For example, Long et al [ 15 ] proposed that PNR might be an indicator of blood hyperco-agulable state, and an increased PNR level may induce a gastric cancer-related ischemic stroke. However, the relationship between PNR and the prognosis of IVT patients has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells can activate the body's coagulation mechanism by releasing many tissue factors, cancer-associated procoagulant, and cyokines, and cancer cells also can interact with platelets to release ADP, arachidonic acid, 5-HT, and other substances to promote blood coagulation. Eventually, the body will be hypercoagulable [23][24][25][26][27]. Bang's recent research showed circulating tumor extracellular vesicles, especially in adenocarcinoma patients, also played a vital role in cancer-associated thrombosis and tumor progression [28,29].…”
Section: Discussionmentioning
confidence: 99%